Pengaruh Media Pembelajaran Puzzle Suku Kata Terhadap Kemampuan Membaca Siswa Mata Pelajaran Bahasa Indonesia Kelas 1 SDN 88 Pekanbaru - Andryani, Irgi Lisa; Rahmi, Laili (Jayapangus Press, 2025)
This study aims to determine the effect of syllable puzzle learning media on the reading skills of first-grade students at SDN 88 Pekanbaru. The background of this research is based on the low early reading ability of students and the prevalent use of conventional teaching methods that are less engaging and not suited to the characteristics of young learners. The research method used is a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The sample consisted of 28 first-grade students selected through purposive sampling. Data were collected through observation and reading tests, while data analysis was conducted using descriptive statistics and paired sample t-test with the help of SPSS software. The results showed an increase in the average score from 35.71 in the pretest to 89.00 in the posttest. The paired t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant effect of using syllable puzzle media on students' reading ability. This media proved to enhance not only reading skills but also students' motivation and engagement during the learning process. Therefore, syllable puzzle media is recommended as an innovative strategy for teaching Indonesian language in early grade classes.